(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article discusses the creation of the play Combate: corpos mortos, vivos e por vir. The staging problematized sexism and racism and the work involved professors, drama graduate students and local artists. It was produced by means of a collaborative creation process in the extreme South of Brazil. Here are presented some aspects of research in performing arts and also those related to the practical creative processes of staging and dramatic writing in contemporaneity. Béatrice Picon-Vallin and Antônio Araújo were the references for the idea of collaborative creation, Oscar Cornago for the notion of participation and, finally, Haroldo de Campos for the concept of transcreation.